Volcanic suppression of Nile summer flooding triggers revolt and constrains interstate conflict in ancient Egypt. Issue 1 (December 2017) - Manning, Joseph; Ludlow, Francis; Stine, Alexander; Boos, William; Sigl, Michael; Marlon, Jennifer
Abstract Volcanic eruptions provide tests of human and natural system sensitivity to abrupt shocks because their repeated occurrence allows the identification of systematic relationships in the presence of random variability. Here we show a suppression of Nile summer flooding via the radiative and dynamical impacts of explosive volcanism on the African monsoon, using climate model output, ice-core-based volcanic forcing data, Nilometer measurements, and ancient Egyptian writings. We then examine the response of Ptolemaic Egypt (305–30 BCE), one of the best-documented ancient superpowers, to volcanically induced Nile suppression. Eruptions are associated with revolt onset against elite rule, and the cessation of Ptolemaic state warfare with their great rival, the Seleukid Empire. Eruptions are also followed by socioeconomic stress with increased hereditary land sales, and the issuance of priestly decrees to reinforce elite authority. Ptolemaic vulnerability to volcanic eruptions offers a caution for all monsoon-dependent agricultural regions, presently including 70% of world population. The degree to which human societies have responded to past climatic changes remains unclear. Here, using a novel combination of approaches, the authors show how volcanically-induced suppression of Nile summer flooding led to societal unrest in Ptolemaic Egypt (305–30 BCE).